2013
DOI: 10.3109/17482941.2013.781190
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia in acute ST-segment elevation myocardial infarction is a marker of left ventricular remodeling

Abstract: SH is associated with high in-hospital mortality risk and it could be marker of LV remodeling (significant increase of EDV during one year).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
2
7
0
4
Order By: Relevance
“…They demonstrated that corrected thrombolysis in myocardial infarction (TIMI) frame counts were significantly higher in patients with acute hyperglycemia and were independently associated with plasma glucose level. Moreover, SH is a marker of left ventricular (LV) remodeling, which may help explain postinfarction transition to LV failure 35 . The presence of acute hyperglycemia was associated with the impairment of epicardial coronary flow after primary stent implantation.…”
Section: The Presence Of Stress Hyperglycemia Association With Almostmentioning
confidence: 99%
“…They demonstrated that corrected thrombolysis in myocardial infarction (TIMI) frame counts were significantly higher in patients with acute hyperglycemia and were independently associated with plasma glucose level. Moreover, SH is a marker of left ventricular (LV) remodeling, which may help explain postinfarction transition to LV failure 35 . The presence of acute hyperglycemia was associated with the impairment of epicardial coronary flow after primary stent implantation.…”
Section: The Presence Of Stress Hyperglycemia Association With Almostmentioning
confidence: 99%
“…Rezultai našeg istraživanja pokazuju da je glikemija pri prijemu ≥8 mmol/L kod pacijenata bez prethodnog DM, povećala rizik intrahospitalnog mortaliteta 6,4 puta, a jednogodišnjeg mortaliteta oko 2 puta. 20 U retrospekivnoj analizi urađenoj na 141680 starijih pacijenata sa AIM, hiperglikemija je bila česta, retko treirana, i udružena sa značajno većim rizikom intrahospitalnog i jednogodišnjeg mortaliteta kod pacijenata bez prethodno poznatog DM u odnosu na dijabeičare. Visok rizik perzisira i nakon korekcije za komorbiditete (prethodni infarkt i srčana insuicijencija) i težinu bolesi (viša Killip klasa, veći pik CK, viši nivo kreainina, niža EF), 2 što upućuje na moguću kauzalnost.…”
Section: Intrahospitalni I Jednogodišnji Mortalitetunclassified
“…31 U našem istraživanju, na 275 pacijenata sa STEMI, pokazano je da SH uiče na remodelovanje LK kod pacijenata bez prethodnog DM, procenjeno ehokardiografski značajnim povećanjem EDV tokom godinu dana. 20 Može se zaključii da među do sada objavljenim istraživanjima na temu povezanosi SH i remodelovanja LK postoje brojne metodološke razlike. Uključivani su pacijenta sa STEMI, ali i svi pacijeni sa AIM ili samo pacijeni sa STEMI prednjeg zida, pacijeni sa uspešnom reperfuzijom ili bez reperfuzije, pacijeni lečeni trombolizom ili primarnom PCI.…”
Section: Funkcija Leve Komoreunclassified
See 2 more Smart Citations